2013
DOI: 10.3201/eid1911.130777
|View full text |Cite
|
Sign up to set email alerts
|

Mayaro Virus Infection, Amazon Basin Region, Peru, 2010–2013

Abstract: During 2010–2013, we recruited 16 persons with confirmed Mayaro virus infection in the Peruvian Amazon to prospectively follow clinical symptoms and serologic response over a 12-month period. Mayaro virus infection caused long-term arthralgia in more than half, similar to reports of other arthritogenic alphaviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 14 publications
1
102
0
8
Order By: Relevance
“…Our future work will focus on longer follow-up times and quality of life, as we have done for other arboviruses. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our future work will focus on longer follow-up times and quality of life, as we have done for other arboviruses. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The 7.7% frequency of symptom persistence in our DENV-infected subjects was less than what we observed in febrile controls and lower than what prior studies reported in infection with other arboviruses. 23,[33][34][35][36] However, assuming 96 million people suffer from acute, symptomatic DENV infection annually, this represents a potential disease burden of 7.4 million cases, a substantial number. 1 We hope that our results will better inform patients-and their family members, physicians, and employers-of what to expect in the weeks after DENV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Human infections caused by MAYV have been described in several countries, including Trinidad, 12 Bolivia, 13,14 French Guiana, 15 Peru, 14,16 Venezuela, 17 and Brazil. 7,18,19 In 1978, during an epidemic in Belterra, Pará State, Brazil, the virus was isolated from 43 patients.…”
mentioning
confidence: 99%
“…Samples were collected and archived as part of a study to determine the etiology of febrile illnesses in Latin America. The criteria for inclusion in this study required subjects to present to selected health facilities with an elevated temperature (Ն38°C oral, tympanic, or (Table 2) as previously described (11,17,23). For positive samples, convalescent-phase samples were collected within 10 to 30 days postdiagnosis and EIAs for IgM and IgG were performed as previously described (Table 2) (11,17).…”
Section: Methodsmentioning
confidence: 99%